Recycling process of waste graphite negative plate of lithium ion battery

Through the processes of crushing, spheroidization repair, graphitization treatment and demagnetization grading, the problems of low efficiency and poor environmental protection of graphite negative electrode materials in the existing technology are solved, and efficient and environmentally friendly graphite powder recycling is achieved, which is suitable for large-scale industrialization use.

CN119481402APending Publication Date: 2025-02-18SHENZHEN XINMAO NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411624994.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The methods for recycling graphite negative electrode materials in the prior art have problems such as low recycling efficiency, complex process flow, and poor environmental protection of the process, and are not suitable for large-scale industrial use.

Method used

The graphite negative electrode sheet of the used lithium-ion battery was crushed and passed through a 150-300 mesh screen. After spheroidization repair, graphitization treatment, demagnetization, and grading screening, the negative graphite powder of lithium-ion battery with a particle size of 6.5-32μm was obtained. . This process does not require manual removal of copper foil or the use of chemical reagents in advance, significantly improving recycling efficiency, simplifying the process flow, and enhancing environmental protection.

Benefits of technology

The effective separation of graphite powder and copper powder is achieved, the recycling efficiency is improved, the process flow is simplified, and the environmental protection is enhanced. The obtained graphite powder has high spheroidization, tap density and graphitization, and is suitable for the negative electrode of lithium-ion battery. Good electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481402A_ABST
    Figure CN119481402A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion battery negative electrode material recovery, and particularly discloses a recovery process of a waste graphite negative electrode plate of a lithium ion battery. The recycling process comprises the following steps: S1, crushing a graphite negative electrode plate of the waste lithium ion battery, and sieving with a 150-300-mesh sieve to obtain recycled graphite powder; and S2, carrying out spheroidizing repair, graphitization treatment, demagnetization and grading screening on the recycled graphite powder to obtain the lithium ion battery negative electrode graphite powder with the particle size of 6.5-32 microns. According to the recovery technology, effective separation of the graphite powder and the copper powder is achieved, the recovery efficiency is remarkably improved, the technological process is simplified, no chemical reagent is used in the recovery technology, the environmental protection property of the technological process is enhanced, and the recovery technology is suitable for large-scale industrial use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of recycling negative electrode materials of lithium-ion batteries, and more specifically, it relates to a recycling process for waste graphite negative electrode sheets of lithium-ion batteries. Background Art

[0002] As a new energy storage power source, lithium-ion batteries have developed rapidly since they entered commercialization in the 1990s, gradually replacing lead-acid, nickel-hydrogen and other batteries, and have occupied a dominant position in electronic products such as mobile phones, notebooks and cameras. Due to the advantages of lithium-ion batteries such as high energy density, no memory effect, long service life, and green environmental protection, they have now been applied to the automotive field as a new energy source. At present, the negative electrode material used in commercial lithium-ion batteries is mainly carbon material, with a theoretical specific capacity of 372mAh / g. Among various carbon materials, graphite is the most widely used negative electrode material.

[0003] The service life of lithium-ion batteries is about 3-5 years. Since 2019, my country has officially entered the stage of large-scale retirement of power lithium-ion batteries. According to data from relevant agencies, the total amount of retired power lithium-ion batteries in my country has reached 200,000 tons in 2020, and the amount of retired lithium-ion batteries will reach 640,000 tons by 2025. If a large number of waste lithium-ion batteries are not handled properly, it will cause serious harm to the environment, waste resources, and even pose a serious threat to human health.

[0004] At present, improving resource utilization by recycling and reusing various parts of lithium-ion batteries has attracted widespread attention. However, many studies have focused on recycling high-cost cathode materials (such as LiCoO 2 、LiFePO 4 However, the recovery of graphite from spent lithium-ion batteries is crucial for resource recovery and environmental protection.

[0005] Chinese patent CN 113131029A discloses a method for recycling graphene from graphite negative electrodes of lithium ion batteries, which pre-expands the negative electrode sheets of waste lithium ion batteries with water or dilute hydrochloric acid, separates copper foil and graphite, and then neutralizes the graphite dispersion, separates solid and liquid, pickles and dries the dispersion to obtain graphite powder with high purity. However, this method uses a lot of acid solution, which will corrode the equipment and shorten the service life of the equipment, and the whole process is relatively complicated. Chinese patent CN109742475A discloses a method for recycling negative electrode materials of waste lithium ion batteries, which first uses a scraper to separate the negative electrode sheets of waste lithium ion batteries from the copper foil, then uses ethanol, acetone, dimethyl carbonate or water as a cleaning agent to clean the obtained negative electrode powder, and then removes impurities from the graphite powder through drying, high-temperature calcination and other processes, and the obtained graphite is used as a negative electrode material in sodium ion or potassium ion batteries to obtain good electrochemical performance. However, this method uses manual processing of graphite, the recovery efficiency is low, and the organic solvent is easy to cause harm to the human body.

[0006] In summary, the methods for recycling graphite negative electrode materials in the prior art have problems such as low recycling efficiency, complex process flow, and poor environmental protection of the process, and are not suitable for large-scale industrial use. Summary of the invention

[0007] In order to solve the above technical problems, the present application provides a process for recycling waste graphite negative electrode sheets of lithium-ion batteries.

[0008] In the first aspect, the present application provides a recycling process for waste graphite negative electrode sheets of lithium-ion batteries, which adopts the following technical solution: A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. The graphite negative electrode sheet of the waste lithium-ion battery is crushed and passed through a 150-300 mesh sieve to obtain recycled graphite powder; S2. The recovered graphite powder is subjected to spheroidization repair, graphitization treatment, demagnetization, and grading screening to obtain lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32 μm.

[0009] By adopting the above technical scheme, the present application first directly crushes the graphite negative electrode sheet of the waste lithium-ion battery and passes it through a sieve of a specific mesh number. Due to the different ductility of graphite materials and copper materials, the powder particle size distribution obtained by the two under the same crushing conditions is different. Therefore, the copper powder and other foreign matter in the negative electrode sheet can be effectively removed, and the good separation of graphite powder and copper powder is achieved. Then the recovered graphite powder is repaired by spheroidization and graphitized under the protection of inert gas to restore the electrical conductivity, mechanical properties, thermal conductivity and other characteristics of the graphite powder. After that, the large-particle graphite powder and most of the magnetic metal foreign matter are removed by demagnetization and graded screening to obtain graphite powder that can be used for the negative electrode of lithium-ion batteries. The recycling process of the present application does not need to manually remove the copper foil in advance, or use any chemical reagent to separate the copper foil, so that the graphite powder and the copper powder can be effectively separated, which significantly improves the recovery efficiency and simplifies the process flow. In addition, the recycling process of the present application does not use any chemical reagents, which enhances the environmental protection of the process and is suitable for large-scale industrial use.

[0010] Preferably, in step S2, the rotation speed of spheroidization repair is 3600-6000 r / min, and the time is 30-150 min.

[0011] By adopting the above technical solution, the present application controls the rotation speed and time of the spheroidization repair process, so that the graphite powder of the present application has a higher spheroidization degree and tap density. Graphite powder particles with high spheroidization degree and high tap density can be more closely stacked together, so that the prepared negative electrode slurry is more uniform and dense, and easy to coat on the negative electrode sheet. In addition, the negative electrode prepared with the negative electrode slurry has a more uniform and dense electrode structure, which increases the effective contact area of ​​the negative electrode, improves the electrode capacity of the negative electrode, and the negative electrode surface is smooth and flat, reducing the interface resistance, thereby comprehensively improving the electrochemical performance of the lithium-ion battery.

[0012] Preferably, the rotation speed of the spheroidization repair is 5400-6000r / min, and the time is 120-150min.

[0013] Preferably, the rotation speed of the spheroidization repair is 6000r / min and the time is 150min.

[0014] By adopting the above technical solution, the present application optimizes the rotation speed and time of spheroidization repair, thereby further improving the spheroidization degree and tap density of graphite powder, thereby improving the electrochemical performance of lithium-ion batteries.

[0015] Preferably, the temperature of the graphitization treatment is 2500-3500° C. and the time is 4-8 hours.

[0016] By adopting the above technical solution, the present application controls the temperature of the graphitization treatment, so that the graphite powder of the present application has a higher degree of graphitization, the crystal structure of the graphite powder is more ordered, the lattice arrangement is more complete, and at this temperature, impurities in the recycled graphite powder, as well as the residual binder on the surface and the residual electrolyte inside can be further removed, thereby further improving the purity of the graphite powder and further improving the electrochemical performance of the lithium-ion battery.

[0017] Preferably, the temperature of the graphitization treatment is 3100-3500°C.

[0018] Preferably, the temperature of the graphitization treatment is 3500°C.

[0019] By adopting the above technical solution, the present application optimizes the temperature of graphitization treatment, thereby further improving the graphitization degree and purity of graphite powder, thereby improving the electrochemical performance of lithium-ion batteries.

[0020] Preferably, in step S1, the frequency of crushing is 30-45 Hz.

[0021] By adopting the above technical solution, the particle size distribution of the pulverized graphite powder of the present application is between 2-50 μm, and the particle size distribution of the copper powder is between 110-120 μm. The particle size distribution of the two is quite different, which is conducive to the separation of the two.

[0022] Preferably, the frequency of the crushing is 45 Hz.

[0023] By adopting the above technical solution, the present application optimizes the frequency of crushing, so that the D50 particle size of the graphite powder is 10.4μm, which is convenient for subsequent processing. At this frequency, the crushing efficiency of the powder can reach 78.5%, which significantly improves the recovery efficiency and shortens the recovery time.

[0024] In a second aspect, the present application provides a lithium ion battery negative electrode graphite powder obtained by the above-mentioned recycling process, wherein the sphericity of the lithium ion battery negative electrode graphite powder is not less than 0.78 and the tap density is not less than 0.75g / cm 3 , the ash content is not higher than 0.2%, and the degree of graphitization is not less than 93%.

[0025] By adopting the above technical solution, the properties of the negative electrode graphite powder of the lithium ion battery of the present application are almost the same as those of the commercial graphite powder used for the first time, so that the prepared lithium ion battery can have good electrochemical properties.

[0026] In summary, the present application has the following beneficial technical effects: 1. The recycling process of the present application does not require manual removal of copper foil in advance, or the use of any chemical reagents to separate copper foil, and can effectively separate graphite powder from copper powder, significantly improving the recycling efficiency and simplifying the process flow. In addition, the recycling process of the present application does not use any chemical reagents, which enhances the environmental friendliness of the process and is suitable for large-scale industrial use. 2. The sphericity of the lithium-ion battery negative electrode graphite powder obtained by the recycling process of this application is not less than 0.78, and the tap density is not less than 0.75g / cm 3 , the ash content is not higher than 0.2%, and the degree of graphitization is not less than 93%, which is almost the same as the properties of commercial graphite powder used for the first time, so that the prepared lithium-ion battery has good electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a scanning electron microscope image of the recovered graphite powder obtained in step S1 of Example 1; FIG2( a) is a scanning electron microscope image of the negative electrode graphite powder of the lithium ion battery of Example 1.4; FIG2( b ) is a scanning electron microscope image of the negative electrode graphite powder of the lithium ion battery of Example 2.4; FIG2( c ) is a scanning electron microscope image of the negative electrode graphite powder of the lithium ion battery of Example 3.1; FIG2( d ) is a scanning electron microscope image of the negative electrode graphite powder of the lithium ion battery of Example 3.2; FIG2( e ) is a scanning electron microscope image of the negative electrode graphite powder of the lithium ion battery of Example 3.3; FIG2( f) is a scanning electron microscope image of the negative electrode graphite powder of the lithium ion battery of Example 3.4; FIG3( a) is an XRD diagram of the recovered graphite powder obtained in step S1 of Example 1; FIG3( b) is an XRD diagram of the negative electrode graphite powder of the lithium ion battery of Example 3.5; FIG3( c ) is an XRD diagram of the negative electrode graphite powder of the lithium ion battery of Example 4.1; FIG3( d ) is an XRD diagram of the negative electrode graphite powder of the lithium ion battery of Example 4.2; FIG3( e ) is an XRD diagram of the negative electrode graphite powder of the lithium ion battery of Example 4.3; Figure 3(f) is the XRD pattern of the negative electrode graphite powder of the lithium ion battery of Example 4.4. DETAILED DESCRIPTION

[0028] The present application is further described in detail below in conjunction with the accompanying drawings, embodiments, comparative examples and application examples.

[0029] Example 1.1 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a grinder, grind it at a host frequency of 30 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 3600r / min for 30min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0030] Example 1.2 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a grinder, grind it at a host frequency of 35 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 3600r / min for 30min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0031] Example 1.3 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a grinder, grind it at a host frequency of 40 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 3600r / min for 30min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0032] Example 1.4 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 3600r / min for 30min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0033] Example 2.1 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 4200r / min for 30min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0034] Example 2.2 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 4800r / min for 30min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0035] Example 2.3 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 5400r / min for 30 minutes, and then graphitized at a temperature of 2500°C for 4 hours under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0036] Example 2.4 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 30min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0037] Example 2.5 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6600r / min for 30min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0038] Example 3.1 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 60min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0039] Example 3.2 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 90min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0040] Example 3.3 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 120min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0041] Example 3.4 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 150min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0042] Example 3.5 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 180min, and then graphitized at a temperature of 2500°C for 4h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0043] Example 4.1 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 150min, and then graphitized at a temperature of 2700°C for 8h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0044] Example 4.2 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 150min, and then graphitized at a temperature of 3100°C for 6h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0045] Example 4.3 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 150min, and then graphitized at a temperature of 3300°C for 6h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0046] Example 4.4 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 150min, and then graphitized at 3500°C for 6h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0047] Example 4.5 A recycling process for waste graphite negative electrode sheets of lithium-ion batteries comprises the following steps: S1. Put the graphite negative electrode sheet of the waste lithium-ion battery into a pulverizer, crush it at a host frequency of 45 Hz to obtain a powder, and then put the powder into an ultrasonic vibration screen with a 150-mesh screen to separate and obtain recycled graphite powder; S2. The recovered graphite powder is first spheroidized at a spheroidizing wheel speed of 6000r / min for 150min, and then graphitized at 3700°C for 8h under the protection of a nitrogen atmosphere. After demagnetization and graded screening, lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32μm is obtained.

[0048] Comparative Examples 1.1-1.4 The difference from Examples 1.1-1.4 is that in step S1, an ultrasonic vibrating screen is not used, but the powder is placed in a cyclone separator for separation to obtain recycled graphite powder.

[0049] Comparative Examples 2.1-2.4 The difference from Examples 1.1-1.4 is that in step S1, the screen of the ultrasonic vibration screen is 130 meshes.

[0050] Comparative Examples 3.1-3.4 The difference from Examples 1.1-1.4 is that in step S2, the temperature of the graphitization treatment is 2000°C.

[0051] Performance Testing 1. The tap density, sphericity, degree of graphitization and ash content of the recovered graphite powder obtained in step S1 and the lithium ion battery negative electrode graphite powder obtained in step S2 in the recycling processes of Examples 1-4 and Comparative Examples 1-3 were respectively detected and recorded in Table 1.

[0052] 2. The pulverization efficiency of the pulverization process in step S1 of the recycling process of Examples 1.1-1.4 and the D50 particle size of the graphite powder after pulverization were detected and calculated respectively, and recorded in Table 2.

[0053] 3. Calculate the yield of the spheroidization process in step S2 in the recycling process of Example 1.4, Example 2.1-2.5 and Example 3.1-3.5 respectively, and record it in Table 3.

[0054] Table 1 Table 2 project Graphite powder D50 particle size Crushing efficiency (%) Example 1.1 10.8 22.5 Example 1.2 11.1 42.2 Example 1.3 9.2 66.7 Example 1.4 10.4 78.5 Table 3 From Table 1 and Figure 1 As shown in Figure 2(a), the tap density of the lithium-ion battery negative electrode graphite powder obtained by the recycling process of Example 1 of the present application is 0.963-0.969 g / cm 3 The sphericity is above 0.79, the graphitization degree is not less than 93%, and the ash content is less than 0.2%, indicating that the lithium ion battery negative electrode graphite powder obtained by the recycling process of the present application has a high purity, and the effective separation of graphite powder and copper powder is achieved, and the purpose of recycling graphite powder to the greatest extent is achieved. The difference between Examples 1.1-1.4 is that the host frequency of the pulverization process is different. It can be seen from Table 2 that as the host frequency increases, the pulverization efficiency also increases. Among them, when the host frequency is 45Hz, the pulverization efficiency can reach 78.5%, and the D50 particle size of the recovered graphite powder is controlled at 10.4μm, which is convenient for later processing.

[0055] The difference between Examples 2.1-2.5 and Example 1.4 is that the speed of the spheroidization treatment is different. It can be seen from Table 1 that as the speed of the spheroidization treatment increases from 3600r / min to 6000r / min, the tap density of the graphite powder increases by 6.30% and the sphericity increases by 5.42%; and it can also be seen from Figures 2(a) and 2(b) that as the speed of the spheroidization treatment increases, the spheres of the graphite powder become more saturated and rounded. However, when the speed continues to increase from 6000r / min to 6600r / min, the tap density and sphericity of the graphite powder have almost no change, and it can be seen from the data of Examples 1.4 and 2.5 in Table 3 that when the speed continues to increase from 6000r / min to 6600r / min, the yield of the spheroidization treatment decreases by 2.78%, which shows that the present application can achieve the best level of spheroidization effect and yield of graphite powder by optimizing the speed of the spheroidization treatment process.

[0056] The difference between Examples 3.1-3.5 and Example 2.4 is that the time of spheroidization treatment is different. It can be seen from Table 1 that as the time of spheroidization treatment increases from 30min to 150min, the tap density of graphite powder increases by 5.83% and the sphericity increases by 6.57%; and in combination with Figures 2(b)-(f), it can also be seen that as the time of spheroidization treatment increases, the flat particles in the particle group of graphite powder decrease, the surface becomes more rounded, the fluidity of the particles is increased, and the filling between particles tends to be more adaptive. However, when the time is continued to increase from 150min to 180min, the tap density and sphericity of graphite powder have almost no change, and in combination with the data of Examples 2.4 and Examples 3.1-3.5 in Table 3, it can be seen that as the time of spheroidization treatment increases, the yield of spheroidization treatment gradually decreases. When the time reaches 180min, the yield of spheroidization treatment is only 60%, which shows that the present application can achieve a balance between the spheroidization effect and the yield of graphite powder by optimizing the time of spheroidization treatment process.

[0057] The difference between Examples 4.1-4.5 and Example 3.4 is that the temperature of the graphitization treatment is different. It can be seen from Table 1 and Figures 3(a)-(f) that as the temperature of the graphitization treatment increases from 2500°C to 3500°C, the graphitization degree of the graphite powder increases by 2.47% and the ash content decreases by 78.95%. The test data show that as the temperature of the graphitization treatment increases, the higher the graphitization degree of the graphite powder, the more ordered the crystal structure is, and the more complete the lattice arrangement is. However, when the temperature of the graphitization treatment is further increased from 3500°C to 3700°C, the graphitization degree and ash content of the graphite powder are almost unchanged, which shows that the present application can improve the graphitization degree and purity of the graphite powder by optimizing the temperature of the graphitization treatment, while reducing the energy consumption of the high temperature process.

[0058] The difference between Comparative Example 1.1-1.4 and Example 1.1-1.4 is that a cyclone separator is used instead of an ultrasonic vibrating screen to separate graphite powder and copper powder. As can be seen from Table 1, the ash content of the graphite powder in Comparative Example 1.1-1.4 is 1.49-1.52%, which is 684.21-700% higher than that in Example 1.1-1.4. The test data show that the cyclone separator cannot separate graphite powder and copper powder well, which significantly affects the purity of the graphite powder.

[0059] The difference between Comparative Examples 2.1-2.4 and Examples 1.1-1.4 is that the mesh size of the ultrasonic vibrating screen is too large. As can be seen from Table 1, the ash content of the graphite powder in Comparative Examples 2.1-2.4 is 1.48-1.53%, which is 678.95-705.26% higher than that in Examples 1.1-1.4. Experimental data show that if the mesh size is too large, impurities such as copper foil may be introduced, thereby affecting the purity of the graphite powder.

[0060] The difference between Comparative Examples 3.1-3.4 and Examples 1.1-1.4 is that the temperature of the graphitization treatment is lower than 2500°C. As can be seen from Table 1, the graphitization degree of the graphite powder of Comparative Examples 3.1-3.4 is 91.9-92.2%, which is 0.86-1.18% lower than that of Examples 1.1-1.4, and the ash content is 1.13-1.15%, which is 494.74-505.26% higher than that of Examples 1.1-1.4. Therefore, the experimental data show that if the temperature of the graphitization treatment is too low, it will affect the graphitization degree and purity of the graphite powder.

[0061] Application Examples The performance of lithium-ion battery negative electrode graphite powder is tested using a half-cell test method. The specific method is as follows: (1) The graphite powder or commercial graphite obtained in Example 4.4 was mixed with conductive carbon black and polyvinylidene fluoride in a weight percentage of 94.5:1.5:4, and then an appropriate amount of N-methylpyrrolidone was added. After mixing evenly, the mixture was coated on a copper foil, and then placed in a vacuum drying oven at 120°C for vacuum drying for 4 hours to obtain an electrode sheet; wherein the commercial graphite was from Shenzhen Beite; (2) A metal lithium sheet was used as the positive electrode, a polypropylene microporous membrane was used as the diaphragm, the electrode sheet obtained in step (1) was used as the negative electrode, and a 1 mol / L mixed solution of LiPF6+EC, DEC, and DMC in a volume ratio of 1:1:1 was used as the electrolyte to assemble a lithium ion battery, and the lithium ion battery was subjected to multiple charge and discharge tests under a Xinwei battery test system, with a charge and discharge voltage range of 0.001-3.15 V and a charge and discharge rate of 0.1C. The results are shown in Table 4.

[0062] Table 4 As can be seen from Table 4, the graphite powder obtained by the recycling process of the present application is applied to lithium-ion batteries, which can make the first discharge specific capacity of the lithium-ion battery reach more than 341 mAh / g and the first efficiency reach more than 94%, which is similar to the effect of commercial graphite and has better electrochemical performance.

[0063] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A process for recycling waste graphite negative electrode sheets of lithium-ion batteries, characterized in that: The steps include: S1. The graphite negative electrode sheet of the waste lithium-ion battery is crushed and passed through a 150-300 mesh sieve to obtain recycled graphite powder; S2. The recovered graphite powder is subjected to spheroidization repair, graphitization treatment, demagnetization, and grading screening to obtain lithium-ion battery negative electrode graphite powder with a particle size of 6.5-32 μm.

2. The process for recycling waste graphite negative electrode sheets of lithium ion batteries according to claim 1, characterized in that: In step S2, the rotation speed of the spheroidization repair is 3600-6000 r / min, and the time is 30-150 min.

3. The process for recycling waste graphite negative electrode sheets of lithium ion batteries according to claim 2, characterized in that: The rotation speed of the spheroidization repair is 5400-6000r / min, and the time is 120-150min.

4. The process for recycling waste graphite negative electrode sheets of lithium ion batteries according to claim 3, characterized in that: The rotation speed of the spheroidization repair is 6000r / min and the time is 150min.

5. The process for recycling waste graphite negative electrode sheets of lithium ion batteries according to claim 1, characterized in that: The temperature of the graphitization treatment is 2500-3500° C. and the time is 4-8 hours.

6. The process for recycling waste graphite negative electrode sheets of lithium ion batteries according to claim 5, characterized in that: The temperature of the graphitization treatment is 3100-3500°C.

7. The process for recycling waste graphite negative electrode sheets of lithium ion batteries according to claim 6, characterized in that: The temperature of the graphitization treatment is 3500°C.

8. The process for recycling waste graphite negative electrode sheets of lithium ion batteries according to claim 1, characterized in that: In the step S1, the frequency of the crushing is 30-45 Hz.

9. The process for recycling waste graphite negative electrode sheets of lithium ion batteries according to claim 8, characterized in that: The frequency during the pulverization is 45 Hz.

10. A lithium ion battery negative electrode graphite powder obtained by the recycling process according to any one of claims 1 to 9, characterized in that: The sphericity of the negative electrode graphite powder of the lithium ion battery is not less than 0.78, and the tap density is not less than 0.75g / cm 3 , the ash content is not higher than 0.2%, and the degree of graphitization is not less than 93%.

Citation Information

Patent Citations

  • Recycling method of negative electrode material of waste lithium ion battery

    CN109742475A

  • Method for recycling lithium ion battery graphite negative electrode to regenerate graphene

    CN113131029A

Cited By

  • Asphalt shear-coated graphite negative electrode based on waste graphite and preparation method of asphalt shear-coated graphite negative electrode

    CN120527352A